2010 Ibrahim index of African governance - Mo Ibrahim Foundation
The Ibrahim Index: is funded and led by an African institution, is A frica's leading assessment of governance, provides a framework and too ls for citizens, public authorities and partners to assess progress in governance, compiles 86 indicators grouped into 14 sub-categories and f our, overarching categories to measure the effective delivery of public goods and services to African citizens uses indicators from 23 data pr oviders is made up of over 40,000 raw data points
This document can be accessed on http://www.moibrahimfoundation.org
Its written in English, Arabic, French and portugues
Keywords: Political leadership -- Africa